Dampak Pemberian Kredit Pola Grameen Bank Terhadap Peningkatan Pendapatan Usaha Kecil Masyarakat Pesisir oleh Koperasi Lembaga Ekonomi Pengembangan Pesisir Mikro Mitra Mina di Kabupaten Tuban - Enny Sjafrida Marpaung; Ma'mun Sarma; Wilson Halomoan Limbong (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2013)
One of the main factor which contributes why coastal communities cannot improve their economy is low capital. This is because they have limited access to capital and it might be true that bank give limited credit facilities to fisheries stakeholders. The objectives of this research are to: (1) identify the implementation process of Grameen Bank credit scheme from Lembaga Ekonomi Pengembangan Pesisir Mikro Mina Tani (LEPP-M3) Tuban cooperative; (2) identify constrains faced in giving credit on Grameen Bank scheme; (3) identify benefit offered in giving credit on Grameen Bank scheme; and (4) analyse the impact of giving credit on Grameen Bank scheme on coastal communities income. The sampling technique used is Cluster Sampling technique. Descriptive Statistics, Multiple Linear Regression Analysis and Hypothesis Testing have been carried out to answer the research objective. These Statistics and Analysis have been done to find out the level of knowledge of all members, the level of program implementation and the level of benefits received by members. Meanwhile, the Hypothesis Testing is used to find out the absolute effects in net income of small enterprises before and after Grameen Bank credit scheme has been given. This effects is analysed paired t-test. The results show that the level of knowledge of the members to the LEPP-M3 Cooperative of Grameen Bank scheme is very good. The implementation of Grameen Bank scheme helps greatly the communities in improving their business with reasonable requirements that are not burden to its members. Furthermore, another benefit of Grameen Bank lending scheme for their members is to raise their capital with credit facilities, and they are also accustomed to saving. In installment payments, members do not have to go to the cooperatives LEPP-M3, but cooperative management will visit a weekly meeting place which has been determined. Meanwhile, the results of Paired Samples Test indicate that there a positive correlation between the income of small enterprises before and after Grameen Bank Program. This means that by Grameen Bank scheme from the LEPP-M3 Cooperative Tuban, the income of small businesses increase